(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work Antonio Tovar’s theories about the iberian word śalir are exposed. For us, in agreement with others authors, more than with baskish zilhar ‘silver’, it is related with sari ‘prize’. The European and Mediterranean conexions for śalir exposed by Tovar can’t, in fact, be verified.